Bat-borne H9N2 influenza virus evades MxA restriction and exhibits efficient replication and transmission in ferrets - Halwe, Nico Joel; Hamberger, Lea; Sehl-Ewert, Julia; Mache, Christin; Schön, Jacob; Ulrich, Lorenz; Calvelage, Sten; Tönnies, Mario; Fuchs, Jonas; Bandawane, Pooja; Loganathan, Madhumathi; Abbad, Anass; et al. (Nature communications, 2024)
Influenza A viruses (IAVs) of subtype H9N2 have reached an endemic stage in poultry farms in the Middle East and Asia. As a result, human infections with avian H9N2 viruses have been increasingly reported. In 2017, an H9N2 virus was isolated for the first time from Egyptian fruit bats ( Rousettus aegyptiacus ). Phylogenetic analyses revealed that bat H9N2 is descended from a common ancestor dating back centuries ago. However, the H9 and N2 sequences appear to be genetically similar to current avian IAVs, suggesting recent reassortment events. These observations raise the question of the zoonotic potential of the mammal-adapted bat H9N2. Here, we investigate the infection and transmission potential of bat H9N2 in vitro and in vivo, the ability to overcome the antiviral activity of the human MxA protein, and the presence of N2-specific cross-reactive antibodies in human sera. We show that bat H9N2 has high replication and transmission potential in ferrets, efficiently infects human lung explant cultures, and is able to evade antiviral inhibition by MxA in transgenic B6 mice. Together with its low antigenic similarity to the N2 of seasonal human strains, bat H9N2 fulfils key criteria for pre-pandemic IAVs. In this study, the authors report that bat H9N2 influenza A virus replicates and transmits in ferrets, efficiently infects human lung explant cultures, evades MxA antiviral activity in mice, and has low antigenic similarity to seasonal N2, meeting pre-pandemic criteria.